1975
DOI: 10.1161/01.str.6.2.136
|View full text |Cite
|
Sign up to set email alerts
|

Brain Scanning in Cerebral Vascular Disease: A Reappraisal

Abstract: Abstract:Brain Scanning in Cerebral Vascular Disease: A Reappraisal• The frequency of abnormal brain scans in patients with cerebral vascular disease admitted to a stroke intensive care unit has been evaluated in relation to diagnosis, time after onset of symptoms, effect of delayed imaging and the degree of clinical neurological recovery. In patients with completed thromboembolic infarction, 33% had abnormal scans including 39% of those with hemispheric lesions and 14% with posterior fossa lesions. Completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1976
1976
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In our experience 12 abnormal RN images were seen in 43% of patients with intracerebral hematoma. The results in the current study show a lower percentage (28%) and confirm the superiority of CT over RN imaging in this group of patients.…”
Section: Illmentioning
confidence: 56%
See 1 more Smart Citation
“…In our experience 12 abnormal RN images were seen in 43% of patients with intracerebral hematoma. The results in the current study show a lower percentage (28%) and confirm the superiority of CT over RN imaging in this group of patients.…”
Section: Illmentioning
confidence: 56%
“…Welch et al 12 in a study of 169 radionuclide studies in patients with thromboembolic cerebral infarction reported 32% positive studies during the first week after the ictus and 52% positive findings in studies done later than one week after the ictus. They also indicated a 27% incidence of abnormal studies in the first two days after the episode.…”
Section: Illmentioning
confidence: 99%
“…A number of studies compasing CT and 99mTc radionuclide imaging have indicated a similar time course for visualisation of BBB dysfunction in cases of cerebral infarction [19][20][21][22]. The acute phase was most likely to yield negative results and the 10-to 14-day period was considered optimal for obtaining CT enhancement or 99mTc accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Bone imaging agents such as strontium-85, strontium-87m, fluorine-18, technetium-99m-phosphate compounds have been shown to concentrate in pulmonary metastases of osteogenic sarcoma [4,5]. This phenomenon, as in cases 1 and 2, does not appear to be related to radiographically apparent calcification.…”
Section: Discussionmentioning
confidence: 99%
“…The factors influencing the presence or absence of radionuclide uptake are not clear. Localization of bone imaging agents in pulmonary metastases has recently been reported in 80% [5] and 100% [4] of patients. Thus, bone scintigraphy is useful in selected patients with osteogenic sarcoma metastatic to lung.…”
Section: Discussionmentioning
confidence: 99%